B241 Development of thenar eminence compartment syndrome during spinal surgery, and management under regional anaesthesia. (11th August 2022) - Bell, A; Joyce, D; Walsh, L; Maharaj, C
Abstract : Background and Aims: A 44-year-old gentleman was listed for emergency spinal cord decompression and stabilisation of the spine (T4-T9), having presented with cauda equina. He had a background of hypertension, anxiety, depression and BMI of 45 (185cm and 155kg). Methods: He underwent a general anaesthetic. He was difficult to bag-mask ventilate, given his high BMI and thick beard, and was a difficult intubation. Given the nature of the procedure and the need for the specialised spinal bed and O-arm in theatre, the patient's arms were required to be tightly wrapped. We ensured that the arterial line was reading and that intravenous access was maintained. Following a successful surgery and uneventful anaesthesia, the patient was repositioned, awoken and extubated safely. He complained of severe pain localised to his right hand, even on passive movement. The thenar eminence was erythematous and swollen. Compartment syndrome of the thenar eminence was diagnosed. Results: There have been reports of loss of airway patency and failure to re-intubate patients that have been proned. 1 Voluntarily preforming a repeat general anaesthetic was not felt to be the safest option due to him being a difficult intubation, and recent extubation with probable airway odema, and orofacial swelling following 6-hours of being proned. An emergency regional axillary block was performed, and he underwent emergency fasciotomy of his thenar eminence of the right hand. Conclusions: This interesting case demonstrates the need for careful attention to be given to patient positioning intra-operatively, and the appropriate use of regional anaesthesia to provide the safest care for our patient.